Transparency, Translucency, and Obscurity in the Victorian Monologue - Jean-Charles Perquin (Cahiers Victoriens et Edouardiens)
The Victorian dramatic monologue is not only a first person poetic speech with a silent audience suggested in the very poem; it is also a complex poetic chiaroscuro in which the speech itself is translucent, but always on the verge of obscurity, since what is at stake in the poem is the question of understanding. The speaker has to be understood by the reader, whereas the addressee must be partly kept in the dark. In other words, the reader reconstructs the speech in the back of the voiceless listener’s mind, thus adding to the natural difficulty of poetic language. If poetry rests on the maximal use of the possibilities of language, the genre of the dramatic monologue adds to that condition the indirection of speech, i.e. the fact that the addressee has to miss the message the reader has to understand in order to build an intricate mesh of misunderstandings. Such obscure transparency, or transparent obscurity, is the condition for a poetic genre that cannot rely only on form.